Sostoyanie vnutrieritrotsitarnogo metabolisma i srodstvo gemoglobina k kislorodu u basketbolistov - Lutsik, E. G.; Popichev, M. I.; Konoshenko, S. V.; Tavria, V. I. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
The purpose of this work was to study the separate parameters of intraerythrocyte metabolism and affinity of a hemoglobin to oxygenium in sportsman at the competitive season year training cycle. In the process of "long" and "expedited" acclimatization to physical loads the metabolic rearrangements with an enhancement effect after load as a result of educing of compensational-adaptational reactions in erythrocytes are carried out. That is accompanied by the change of function activity of hemoglobin in a direction of promoting more effective transfer the oxygenium to cells.